2017
DOI: 10.1007/978-1-4939-3210-8_6
|View full text |Cite
|
Sign up to set email alerts
|

Paving the Way for Transitions—A Case for Weyl Geometry

Abstract: This paper presents three aspects by which the Weyl geometric generalization of Riemannian geometry, and of Einstein gravity, sheds light on actual questions of physics and its philosophical reflection. After introducing the theory's principles, it explains how Weyl geometric gravity relates to Jordan-Brans-Dicke theory. We then discuss the link between gravity and the electroweak sector of elementary particle physics, as it looks from the Weyl geometric perspective. Weyl's hypothesis of a preferred scale gaug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 120 publications
0
23
0
Order By: Relevance
“…So far this is similar to the well known Jordan-Brans-Dicke (JBD) scalar-tensor theory of gravity [14], [7], [11], [10]. But here we work in a scalar-tensor theory in the framework of Weyl's generalization of Riemannian geometry [2,16,17,22,23]. Crucial for the Weyl geometric scalar tensor approach (WST) is that the scalar curvature R and all dynamical terms involving covariant derivatives are expressed in Weyl geometric scale covariant form.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…So far this is similar to the well known Jordan-Brans-Dicke (JBD) scalar-tensor theory of gravity [14], [7], [11], [10]. But here we work in a scalar-tensor theory in the framework of Weyl's generalization of Riemannian geometry [2,16,17,22,23]. Crucial for the Weyl geometric scalar tensor approach (WST) is that the scalar curvature R and all dynamical terms involving covariant derivatives are expressed in Weyl geometric scale covariant form.…”
Section: Introductionmentioning
confidence: 67%
“…Because of the different profile for the scalar field halo of WST this is a critical step for our exercise. 22 On the other hand, if the resulting systematic errors are smaller than the error intervals of M tot (75), implied by the observational errors of the other quantities, they do not disturb a rough empirical check of the model. The points (1), (2) and (4), in particular the estimate of stellar mass concentrated in galaxies and gas mass, are fairly insensitive against a change of the background theory from Einstein gravity to WST.…”
Section: Theory Dependence Of Mass Data For Galaxy Clustersmentioning
confidence: 96%
“…[4] have shown that, in the WKB approximation, the streamlines of a Klein-Gordon field approximate the geodesics of the Weyl metric if and only if the scale curvature vanishes. 17 [38,37,35,39,2,48].…”
Section: Scale Invariant Observables and Two Distinguished Gaugesmentioning
confidence: 99%
“…In vacuum the r.h.s. of the Einstein equation (47,48) simplifies to the quartic term ("cosmological constant") of the scalar field potential (49):…”
Section: Schwarzschild-de Sitter Solutionmentioning
confidence: 99%
“…The latter indicated, at first glance, an active scaling symmetry of mass/energy in high energy physics; but it turned out to hold only approximatively and was of restricted range. 19 See the discussion in (Quiros et al, 2013b) and (Scholz, 2017). 20 (Weyl, 1920) 21 Weyl's note (Weyl, 1921) became better known by his calculation and discussion of projective and conformal curvature tensors, which followed.22 See (Trautman, 2012).…”
mentioning
confidence: 99%